Civil Wars : Internal Struggles, Global Consequences - Olson Lounsbery, Marie, 1970- (Book collections on Project MUSE., 2009)
What motivates individuals to take up arms against their government? What types of states have historically been more prone to internal conflicts? In Civil Wars: Internal Struggles, Global Consequences Marie Olson Lounsbery and Frederic Pearson explore these questions and present a comprehensive analysis of the causes, consequences, and management potential regarding civil wars throughout the world.